Review – Bacteria and their extracellular polymeric substances causing biofouling on seawater reverse osmosis desalination membranes. (1st October 2018) - Nagaraj, Veena; Skillman, Lucy; Li, Dan; Ho, Goen
Abstract: Biofouling in seawater reverse osmosis (SWRO) membranes is a critical issue faced by the desalination industry worldwide. The major cause of biofouling is the irreversible attachment of recalcitrant biofilms formed by bacteria and their extracellular polymeric substances (EPS) on membrane surfaces. Transparent exopolymer particles (TEP) and protobiofilms are recently identified as important precursors of membrane fouling. Despite considerable amount of research on SWRO biofouling, the control of biofouling still remains a challenge. While adoption of better pretreatment methods may help in preventing membrane biofouling in new desalination setups, it is also crucial to effectively disperse old, recalcitrant biofilms and prolong membrane life in operational plants. Most current practices employ the use of broad spectrum biocides and chemicals that target bacterial cells to disperse mature biofilms, which are evidently inefficient. EPS, being known as the strongest structural framework of biofilms, it is essential to breakdown and disintegrate the EPS components for effective biofilm removal. To achieve this, it is necessary to understand the chemical composition and key elements that constitute the EPS of major biofouling bacterial groups in multi-species, mature biofilms. However, significant gaps in understanding the complexity of EPS are evident by the failure to achieve effective prevention and mitigation of fouling in most cases. Some of the reasons may be difficulty in sampling membranes from fully operational full-scale plants, poor understanding of microbial communities and their ecological shifts under dynamic operational conditions within the desalination process, selection of inappropriate model species for laboratory-scale biofouling studies, and the laborious process of extraction and purification of EPS. This article reviews the novel findings on key aspects of SWRO membrane fouling and control measures with particular emphasis on the key sugars in EPS. As a novel strategy to alleviate biofouling, future control methods may be aimed towards specifically disintegrating and breaking down these key sugars rather than using broad spectrum chemicals such as biocides that are currently used in the industry. Highlights: Membrane biofouling in seawater reverse osmosis desalination-a major problem. Significance of bacterial extracellular polymeric substances, TEP and protobiofilms in fouling. Improved control strategies may be targeted at breakdown of bacterial extracellular polymers.